Synchronous appearance of gastrointestinal stromal tumor and neuroendocrine tumor in stomach: Review of the literature and management strategies - DUMAN, DENİZ; YEGEN, ŞEVKET CUMHUR (AVES, 2012)
Gastrointestinal stromal tumors represent the most common mesenchymal tumor of the digestive tract. Although the stomach is the most common location for gastrointestinal stromal tumor with the co-primary tumors, the synchronous appearance of a neuroendocrine tumor and gastrointestinal stromal tumor in the stomach is rare. We present here the case of a 48-year-old male with gastric well-differentiated neuroendocrine tumor and gastrointestinal stromal tumor discovered incidentally during surgical treatment of the neuroendocrine tumor. We discuss the current guidelines for the management of small gastrointestinal stromal tumors (<2 cm in diameter) and the gastric carcinoids. We also review the literature for the co-occurrence of gastrointestinal stromal tumor and neuroendocrine tumor in a gastric location.
Keywords: Gastrointestinal stromal tumor; neuroendocrine tumor; gastric carcinoid; carcinoid tumor; hypergastrinemia; endoscopic ultrasound; TREATMENT GUIDELINES; COEXISTENCE